Alcohol consumption and risk of urothelial cell bladder cancer in the European prospective investigation into cancer and nutrition cohort. Issue 10 (31st July 2017) - Botteri, E.; Ferrari, P.; Roswall, N.; Tjønneland, A.; Hjartåker, A.; Huerta, J.M.; Fortner, R.T.; Trichopoulou, A.; Karakatsani, A.; La Vecchia, C.; Pala, V.; Perez‐Cornago, A.; et al.
Abstract : Findings on the association between alcohol consumption and bladder cancer are inconsistent. We investigated that association in the European Prospective Investigation into Cancer and Nutrition cohort. We included 476, 160 individuals mostly aged 35–70 years, enrolled in ten countries and followed for 13.9 years on average. Hazard ratios (HR) for developing urothelial cell carcinoma (UCC; 1, 802 incident cases) were calculated using Cox proportional hazards models. Alcohol consumption at baseline and over the life course was analyzed, as well as different types of beverages (beer, wine, spirits). Baseline alcohol intake was associated with a statistically nonsignificant increased risk of UCC (HR 1.03; 95% confidence interval (CI) 1.00–1.06 for each additional 12 g/day). HR in smokers was 1.04 (95% CI 1.01–1.07). Men reporting high baseline intakes of alcohol (>96 g/day) had an increased risk of UCC (HR 1.57; 95% CI 1.03–2.40) compared to those reporting moderate intakes (<6 g/day), but no dose–response relationship emerged. In men, an increased risk of aggressive forms of UCC was observed even at lower doses (>6 to 24 g/day). Average lifelong alcohol intake was not associated with the risk of UCC, however intakes of spirits > 24 g/day were associated with an increased risk of UCC in men (1.38; 95% CI 1.01–1.91) and smokers (1.39; 95% CI 1.01–1.92), compared to moderate intakes. We found no association between alcohol and UCC in women and never smokers. In conclusion, we observed some associations between alcohol and UCC in men and in smokers, possibly because of residual confounding by tobacco smoking. Abstract : What's new? Findings from the EPIC cohort do not suggest a clear detrimental effect of alcohol on bladder cancer risk. However, we found some association between alcohol and risk of the most aggressive forms of bladder cancer in men and in smokers. Among the different beverages, high intakes of spirits were associated with an increased risk of bladder cancer in men and in smokers, while beer and wine were not. Further studies confirming these results are warranted.